2006
DOI: 10.1038/sj.tpj.6500389
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin transporter gene polymorphism is not associated with smoking behavior

Abstract: Nicotine increases serotonin release in the brain and symptoms of nicotine withdrawal may be modulated by diminished serotonergic neurotransmission. The promoter region of the serotonin transporter gene, solute carrier family neurotransmitter transporter member 4 (SLC6A4), contains a functional tandem repeat polymorphism. The long (L) variant is more actively transcribed than the short (S) variant and is associated with a higher serotonin uptake. To investigate the potential role of this polymorphism for smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
3
26
1
Order By: Relevance
“…Thus, polymorphisms present in the gene of the 5-HTT have been increasingly associated with the smoking habit in the last decade and the great majority of these search for association with the 5-HTTLPR polymorphism [30]. However, some research, such as the pioneer study by Lerman et al [31], did not report association of smoking behavior with the 5-HTTLPR polymorphism [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, polymorphisms present in the gene of the 5-HTT have been increasingly associated with the smoking habit in the last decade and the great majority of these search for association with the 5-HTTLPR polymorphism [30]. However, some research, such as the pioneer study by Lerman et al [31], did not report association of smoking behavior with the 5-HTTLPR polymorphism [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Trummer et al [30] suggested that other polymorphisms present in the SLC6A4 gene might be associated with smoking and the STin2 VNTR (5-HTTVNTR2) genetic variant was considered a promising candidate. There are various arguments for associating this polymorphism with smoking, such as the fact that it has a regulatory trait at the transcriptional level of the serotonin transporter, such as 5-HTTLPR.…”
Section: Discussionmentioning
confidence: 99%
“…On balance, the 5-HTT promoter polymorphism seems not to be associated with smoking behavior. 69 The mechanisms underpinning the therapeutic effect of SSRIs remain incompletely understood. The knowledge that neuronal uptake blockade following antidepressant administration occurs rapidly but therapeutic effects may take from 2 to 6 weeks to occur 70 has been difficult to reconcile both in terms of the etiology of the disease and the therapeutic mechanism of SSRIs.…”
Section: Commentmentioning
confidence: 99%
“…122 The evidence for the impact of 5-HTTLPR on smoking has been mixed; the S-allele occurred at a lower frequency in current smokers compared to former or never smokers, 123,124 but others have not found any associations with current smoking, age of smoking initiation, cigarette consumption, Fagerstrom Tolerance Questionaire (FTQ) scores or previous quit history. 125,126 Adolescents with the SS genotype were more likely to be current heavy smokers with earlier onset of smoking. 127 A strong relationship has been observed between the SS genotype and irritability levels, or temperament traits.…”
Section: Serotonin Systemmentioning
confidence: 99%